2012
DOI: 10.1007/s11947-012-0931-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamma Irradiation on the Chemical Composition and Antioxidant Activity of Lactarius deliciosus L. Wild Edible Mushroom

Abstract: The short shelf-life of mushrooms is an obstacle to the distribution and marketing of the fresh product. There has been extensive research on finding the most appropriate technology for mushrooms preservation and a particular interest arises for wild species.Treatment by irradiation emerges as a possible conservation technique that has been tested successfully in several food products. Herein, the effects of gamma irradiation on Lactarius deliciosus (L. ex Fr.) S. F. Gray chemical composition and antioxidant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…In a previous study, our research group reported the effects of gamma irradiation on chemical composition and antioxidant activity of Lactarius deliciosus fresh samples (Fernandes et al, 2013a). The obtained data shown that, until 1 kGy, gamma irradiation might provide a useful alternative to ensure the quality and extend their shelf life, since its effects on the assayed parameters were less significant than the changes caused by storage time.…”
Section: Introductionmentioning
confidence: 94%
“…In a previous study, our research group reported the effects of gamma irradiation on chemical composition and antioxidant activity of Lactarius deliciosus fresh samples (Fernandes et al, 2013a). The obtained data shown that, until 1 kGy, gamma irradiation might provide a useful alternative to ensure the quality and extend their shelf life, since its effects on the assayed parameters were less significant than the changes caused by storage time.…”
Section: Introductionmentioning
confidence: 94%
“…Mushrooms are perishable and have a short shelf life at room temperature (Fernandes et al, 2013). In particular, physiological and microbial changes in fresh-cut mushrooms are accelerated owing to their high respiration rate during storage, resulting in browning and sliminess (Koorapati et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Gamma radiation alone and in combination with refrigeration as a hurdle technology has been proven an efficient way to increase storability and extend the shelf life of numerous fruits and vegetables, such as blueberry (Perkins-Veazie et al, 2008), wild edible mushroom (Fernandes et al, 2013), and ash gourd (Tripathi et al, 2013). As a technique steadily gaining worldwide acceptance, gamma radiation will become a versatile postharvest tool before long (Mahto and Das, 2014).…”
Section: Introductionmentioning
confidence: 99%